English Speaking Difficulties Faced by English Education Students from Rural Areas in Tadulako University - Nurlela Nurlela; Mochtar Marhum; Sukmawati Sadilia; ⁠Abdul Kamaruddin (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to describe the speaking difficulties and their underlying causes experienced by English Education students from rural areas at Tadulako University. The study employed a descriptive qualitative research design involving three first-year students of the English Education Study Program who were selected through snowball sampling. Data were collected through semi-structured interviews and supported by documentary evidence. The data were analyzed using Braun Clarke (2006) thematic analysis. The findings revealed that the participants experienced various speaking difficulties, including limited vocabulary, grammatical problems, pronunciation difficulties, hesitation, frequent pauses, and difficulties organizing ideas. The participants also tended to translate their ideas mentally from their first language into English before speaking, which affected their fluency and confidence. Several factors contributed to these difficulties, particularly speaking anxiety, limited opportunities for speaking practice, and minimal exposure to English outside the classroom. The study concludes that students’ speaking difficulties are influenced by both linguistic and non-linguistic factors. Therefore, supportive learning environments and meaningful opportunities for communication are needed to improve their speaking competence and confidence.